The development and evaluation of a sub-health self-rating scale for university students in China - Jian-lu Bi; Jing Chen; Xiao-min Sun; Xiao-li Nie; Yan-yan Liu; Ren Luo; Xiao-shan Zhao (BMC, 2019)
Abstract Background Sub-health status is defined as declines in vitality, physiological function and capacity for adaptation, but without the presence of clinical or sub-clinical disease. We have developed and evaluated a comprehensive questionnaire, the Sub-Health Self-Rating Scale (SSS), to assess sub-health status in university students. Method The items for the draft questionnaire were discussed in focus groups. The WHOQOL-BREF was selected as the validity reference. From a professional perspective and large sample evaluation, the scale ultimately consisted of 58 items. The reliability and validity of the SSS was examined in undergraduate students and 1000 questionnaires were randomly selected from the samples for expert evaluation. Results Cronbach's α of the total scale was 0.942. The dimensions of physiological, psychological and social had high reliability: 0.915, 0.856 and 0.850, respectively. Based on scree plot and related theories, there were 10 factors to be extracted. The correlation coefficient between the total scale and sub-scale was high. The dimensions of physiological, psychological and social had high correlations with the total scale: 0.929, 0.803 and 0.774, respectively. The sub-health cut-off point of the total scale was 72; for the physiological field, it was 72; for the psychological field, it was 60; and the social field, it was 56. The fit between the expert evaluation method and the scale method was 0.758. The lower the score, the worse the health condition. Conclusion We established and evaluated a valid instrument (SSS) that encompasses physiological, psychological and social factors to investigate sub-health status. It is short and easy to complete, and therefore suitable for use with undergraduate students.